2014
DOI: 10.1002/joc.3970
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic climatology of extreme precipitation in alpine Australia

Abstract: ABSTRACT:Extreme precipitation over the eastern Australia can be significantly enhanced by topographic interaction with the westerly flow. These extreme events can cause severe flooding, damage and disruption to human activities, yet in some areas they are also an invaluable source of water and snow. In this study, we use rain gauge and snowfall accumulation data to investigate connections between extreme rain and snow in alpine Australia and the large-scale climate. These data have been divided into three geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…Hoy et al 2014;Newton et al 2014a, b;Bettolli et al 2010;Stahl et al 2006). Theobald et al (2015) presents a novel, automated approach to classifying year-around synoptic systems across SEA, building upon previous studies which largely focussed on cool-season precipitation, ; Pook et al 2006;Wright 1989, Fiddes et al 2014. In addition to the widely studied cold front and closed low weather systems, Theobald et al (2015) found a strong emphasis on tropical moisture pathways from oceans to the north-east and north-west of Australia for delivering precipitation to the Snowy Mountains region.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Hoy et al 2014;Newton et al 2014a, b;Bettolli et al 2010;Stahl et al 2006). Theobald et al (2015) presents a novel, automated approach to classifying year-around synoptic systems across SEA, building upon previous studies which largely focussed on cool-season precipitation, ; Pook et al 2006;Wright 1989, Fiddes et al 2014. In addition to the widely studied cold front and closed low weather systems, Theobald et al (2015) found a strong emphasis on tropical moisture pathways from oceans to the north-east and north-west of Australia for delivering precipitation to the Snowy Mountains region.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The cool-season synoptic circulation over various regions of SEA has been well studied (e.g., Wright 1989;Pook et al 2006;Landvogt et al 2008;Risbey et al 2009;Gallant et al 2012), although few studies relate specifically to the Snowy Mountains area (Colquhoun 1978;Chubb et al 2011;Fiddes et al 2015). These studies commonly report cool-season precipitation declines.…”
Section: Introductionmentioning
confidence: 99%
“…There are no comparable snow depth data sets for the Victorian mountains, with the best available data (Fiddes et al, 2014a) starting in the 1980s, and hence this study will focus on the New South Wales data. While Victorian seasonal snow depths would be expected to be closely correlated with those in New South Wales, extension of these results to Victoria should be done with some caution, particularly as the weather systems that produce the majority of snowfall may differ across the ranges.…”
Section: Datamentioning
confidence: 99%
“…Nicholls (2005) identified a 10% decline in annual maximum snow depth between 1962 and 2002, with the largest decline in spring (40%), while Davis (2013) identified that the average annual maximum snow depths were 15% lower than the 1961-1990 average during 2001-2010. This decline has occurred despite no significant changes in the average precipitation at nearby stations (Davis 2013) or the frequency of extreme precipitation events (Fiddes et al 2014a), and appears primarily related to enhanced warming over the alpine region. The larger trends in spring come as a result of this season being more marginal, with the warming trend bringing forward the shift of snow accumulation to snow loss.…”
Section: Introductionmentioning
confidence: 96%